The relation between the domains of Information Retrieval and Knowledge Organization in international journals - Araújo, Paula Carina de; Guimarães, José Augusto Chaves; Ferneda, Edberto (Faculdade de Filosofia e Ciências, 2016)
The objective of this research is to analyze the thematic of international scientific production published during the 2006 – 2015 period on Knowledge Organization and Information Retrieval indexed in Web of Science an Scopus databases. This study develops a qualitative and exploratory research of a corpus of 100 papers that establishes a relationship between Knowledge Organization and Information Retrieval. The study also analyses the papers that are part of the corpus and classifies them into three categories, using the dimensions of Knowledge Organization that are considered themes in the Brazilian Congress on Knowledge Organization and Representation organized by the International Society for Knowledge Organization (ISKO): epistemological dimension, applied dimension, social and political dimension. We found that most of the scientific production is concentrated in the applied dimension, which can be explained by the applied characteristic of Information Retrieval. The epistemological dimension is the second recurrent, and the social and political dimension has low incidence, which can be explained once the corpus is formed by the international scientific production and is not reflected in a dimension designed for a Brazilian Congress.